Study of Cgrp-Receptors in Human Isolated Middle Meningeal Arteries Using Bibn4096Bs, Compound 1, and HαCgrp(8-37) - Z. Razzaque; D. Shaw; M. Bock; L. Maskell; J. Pickard; D. Sirinathsinghji; J. Longmore (The Scientific World Journal)
Calcitonin, CGRP, adrenomedullin, and amylin require both CRLR (calcitonin-gene receptor like receptor) and receptor activity modifying proteins (RAMP1, RAMP2, and RAMP3) in different combinations for expression of selective, functional receptors[1]. We investigated whether the antagonists BIBN4096BS[2], Compound 1 (WO98/11128, [3]), and CGRP(8-37) are functionally selective for CGRP receptors in human middle meningeal arteries (HMMA).